Reduced glomerular filtration rate is associated with ascending aortic dilatation in South African chronic kidney disease patients - Hassan, Muzamil; Vachiat, Ahmed; Grinter, Sacha; Manga, Pravin; Duarte, Raquel; Naicker, Saraladevi (African Journal of Nephrology, 2022)
Background: Ascending aortic dilatation (AAD) is an adverse prognostic cardiovascular marker in the general population. There are few data reporting its presence or clinical significance in chronic kidney disease (CKD) patients. The aim of this study was to evaluate ascending aorta dimensions and their correlates in a population of South African CKD patients. Methods: A total of 124 CKD patients and 40 healthy controls were enrolled. Cardiac dimensions, systolic and diastolic function indices, and aortic root diameters were assessed by transthoracic echocardiography. The ascending aorta was measured at four levels (aortic annulus, sinuses of Valsalva, sino-tubular junction, and ascending aorta) and was normalised for body surface area. The prevalence of AAD was assessed in CKD patients compared with the control group. Results: In CKD patients, the ascending aorta dimension was significantly larger than in controls at all four sites of the aorta that were measured. The prevalence of AAD was 6.5% at the annulus, 12.9% at the sinuses, 15.3% at the sino-tubular junction, and 8.9% at the ascending aorta. Overall, 29 patients (23%) had AAD. On multivariate analyses, eGFR was independently associated with AAD (odds ratio 0.980; 95% confidence interval 0.965–0.996; P = 0.014). Conclusion: AAD is a common cardiovascular phenotype in South African CKD patients. Low eGFR was independently associated with AAD, suggesting a direct link between CKD and the development of AAD in South African CKD patients.